2018
DOI: 10.1186/s12951-018-0409-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Injectable hydrogel encapsulating Cu2MnS2 nanoplates for photothermal therapy against breast cancer

Abstract: BackgroundIn order to explore the possibility of treating breast cancer by local photo-therapy, a photothermal agents loaded in situ hydrogel was established. In detail, The Cu2MnS2 nanoplates were prepared by one-pot synthesis and, the thermosensitive Pluronic F127 was used as the hydrogel matrix. The Cu2MnS2 nanoplates and the hydrogel were characterized by morphous, particle size, serum stability, photothermal performance upon repeated 808 nm laser irradiation as well as the rheology features. The therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It has been reported that Cu + -catalyzed Fenton-like has high efficiency in neutral and weakly acidic conditions, and the reaction rate can reach∼160-fold higher than that of Fe 2+ /Fe 3+ . However, copper-based nanomaterials used for CDT of cancer had been seldom reported except the recent self-assembled copper-amino acid nanoparticles. , In addition, copper-based nanomaterials have become one of the research hot-spots because of their strong absorption in the NIR region, good biocompatibility, and excellent photothermal conversion efficiency . Compared with other copper-based materials, Cu 2 Se nanomaterials are particularly interesting not only because they have similar optical absorption in NIR window and great photothermal performance but also owing to the fact that Cu and Se are important trace elements in the human body. , Herein, Cu 2 Se hollow nanocubes (Cu 2 Se HNCs) with strong NIR II absorbance were explored for PTT–CDT synergistic therapy of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Cu + -catalyzed Fenton-like has high efficiency in neutral and weakly acidic conditions, and the reaction rate can reach∼160-fold higher than that of Fe 2+ /Fe 3+ . However, copper-based nanomaterials used for CDT of cancer had been seldom reported except the recent self-assembled copper-amino acid nanoparticles. , In addition, copper-based nanomaterials have become one of the research hot-spots because of their strong absorption in the NIR region, good biocompatibility, and excellent photothermal conversion efficiency . Compared with other copper-based materials, Cu 2 Se nanomaterials are particularly interesting not only because they have similar optical absorption in NIR window and great photothermal performance but also owing to the fact that Cu and Se are important trace elements in the human body. , Herein, Cu 2 Se hollow nanocubes (Cu 2 Se HNCs) with strong NIR II absorbance were explored for PTT–CDT synergistic therapy of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cu 2+ -based hydrogels can be used for cancer therapy due to their cellular toxicity to cancerous cells. 123,124 Therefore, choosing appropriate cation-crosslinkers and suitable doses are necessary. For example, in hydrogels, a maximum Cu concentration of 6.8 mg kg −1 shows no toxic effects on fibroblasts and is considered tolerable for tissue regeneration.…”
Section: Categories Of Cross-linking Strategiesmentioning
confidence: 99%
“…The authors have retracted this article [ 1 ] because of an error in the methodology. Recently, the authors have tested the Cu2MnS2 nanoparticles used in their study by XRD, XPS and TEM mapping and have found that the manganese element was not successfully doped.…”
Section: Retraction Note To: J Nanobiotechnol (2018) 16:83 mentioning
confidence: 99%
“…The original article can be found online at https ://doi.org/10.1186/s1295 1-018-0409-3. *Correspondence: liuchengchengf1@163.com 1 Department of Medical Oncology, The Fifth Affiliated Hospital of Guang-Zhou Medical University, Guangzhou Medical University, Guangzhou 510700, China Full list of author information is available at the end of the article…”
Section: Publisher's Notementioning
confidence: 99%